Customer satisfaction as a mediator between service quality to repurchase intention in online shopping - Silverius Y. Soeharso (Cogent Business & Management, 2024)
Online shopping on e-commerce has become a new pattern for consumers' daily activities. Consumers tend to use e-commerce because of its effectiveness and efficiency, which makes it easier to get the products and services. However, this phenomenon becomes a long-term challenge for companies to maintain sustainable consumer service quality and customer satisfaction during their activity to achieve higher sales. This study aims to find customer satisfaction's role as a mediator between service quality utilitarian and pleasant to repurchase intention—the data collected from 521 samples of participants that are e-commerce users in Indonesia. The researcher accepted the data from the digital questionnaire using Google Forms and analyzed using the Structural Equation Modeling method. The result shows that customer satisfaction significantly becomes a mediator between service quality utilitarian and service quality pleasant to repurchase intention. The research also implied that the company could adopt customer relationship management to enhance consumers' repurchase intention and increase profitability.WTP of carbon offsets is becoming increasingly important considering that the issue of climate change and global warming has become a commitment for every country to contribute to reducing global warming by 1.5 degrees Celsius. Global warming that occurs in the world is largely caused by greenhouse gas emissions released into the atmosphere by individuals, organizations/industries, or other sectors that are considered to contribute to air pollution significantly. One sector that is considered to release a lot of carbon emissions is the transportation sector. This research wants to see how the role of society as subjects and objects affected by climate change and global warming is willing to actively contribute to healthier environmental management in the form of willingness to pay (WTP).
Keywords: 650; Customer Relationship Management; customer satisfaction; repurchase intention; service quality utilitarian; service quality pleasant